The Impact of Monetary Policy in Influencing Foreign Exchange Reserves in Indonesia - Hanitha, Vivin; Angreni, Tri; Hendra (International Journal of Innovation Research in Education, Technology and Management, 2025)
This study aims to analyze the effect of exchange rates, Foreign Direct Investment (FDI), export value, foreign debt, money supply, and inflation on Indonesia's foreign exchange reserves in the period 2004 to 2024. Given The significance of foreign exchange reserves for the stability of the nation's economy, this study uses multiple regression analysis to identify factors that affect Indonesia's foreign exchange reserves. The analysis's findings demonstrate that Indonesia's foreign currency reserves are significantly impacted by all investigated factors at the same time, including the exchange rate, foreign data investment, export value, foreign debt, money supply, and inflation. The coefficient of determination (R²) of 0.97 indicates that 97% of the variation in Indonesia's foreign exchange reserves can be explained by the six independent variables in this regression model. The export value and FDI variables have the most dominant influence, while inflation and foreign debt tend to have a smaller but still significant influence. This study makes a significant contribution to our understanding of the variables affecting Indonesia's foreign exchange reserves and can serve as a guide for policymakers as they develop measures that promote foreign exchange reserve stability, which can bolster Indonesia's economic resilience in the face of international difficulties.